2019
DOI: 10.1097/md.0000000000014114
|View full text |Cite
|
Sign up to set email alerts
|

Common causes of emergency department visits for anaphylaxis in Korean community hospitals

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 28 publications
(37 reference statements)
4
9
0
1
Order By: Relevance
“…The incidence of anaphylaxis was higher in women than in men (p < 0.000), which is consistent with other reports for Europe [11,21]. However, this is contrary to the data from Korea where anaphylaxis developed in men more often, at 65% [24]. The annual incidence per population of the West Pomerania Province falls in the range reported in other European registers (0.0015-0.0079%) [11].…”
Section: Analysis Of Results and Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The incidence of anaphylaxis was higher in women than in men (p < 0.000), which is consistent with other reports for Europe [11,21]. However, this is contrary to the data from Korea where anaphylaxis developed in men more often, at 65% [24]. The annual incidence per population of the West Pomerania Province falls in the range reported in other European registers (0.0015-0.0079%) [11].…”
Section: Analysis Of Results and Discussionsupporting
confidence: 87%
“…The annual incidence per population of the West Pomerania Province falls in the range reported in other European registers (0.0015-0.0079%) [11]. However, in comparison to the data from Korea, the frequency of anaphylaxis in the group of patients reporting to Emergency Department was estimated at 0.01% [24].…”
Section: Analysis Of Results and Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…These studies are reported in Fig 2 . 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 …”
Section: Resultsunclassified
“…In highly exposed populations such as beekeepers, forest rangers and gardeners, 6.9-26% experienced systemic reactions to stings [9][10][11][12] . Since anaphylactic reactions owing to stings of Hymenoptera can cause a rapid death 13 , there is a signi cant component of anxiety in susceptible individuals and they experience signi cant impact on quality of life. A quality of life questionnaire was administered to venom-allergic patients in Spain.…”
Section: Introductionmentioning
confidence: 99%